Experience of 101 patients with coronavirus infectious disease 2019 (COVID-19) at a tertiary care center in Japan. Issue 2 (February 2021) - Yao, Kenta; Hasegawa, Shinya; Tagashira, Yasuaki; Takamatsu, Akane; Uenoyama, Yuki; Shimizu, Keiki; Honda, Hitoshi; Nagai, Yoshiki; Okumura, Koichiro; Onda, Tomoko; Kakutani, Takuya; et al.
Abstract: Introduction: Clusters of novel coronavirus infectious disease of 2019 (COVID-19) have spread to become a global pandemic imposing a significant burden on healthcare systems. The lack of an effective treatment and the emergence of varied and complicated clinical courses in certain populations have rendered treatment of patients hospitalized for COVID-19 difficult. Methods: Tokyo Metropolitan Tama Medical Center, a public tertiary acute care center located in Tokyo, the epicenter of COVID-19 in Japan, has been admitting patients with COVID-19 since February 2020. The present, retrospective, case-series study aimed to investigate the clinical course and outcomes of patients with COVID-19 hospitalized at the study institution. Results: In total, 101 patients with COVID-19 were admitted to our hospital to receive inpatient care. Eleven patients (10.9%) received ECMO, and nine patients (8.9%) died during hospitalization after COVID-19 was diagnosed. A history of smoking and obesity were most commonly encountered among patients with a complicated clinical course. Most patients who died requested to be transferred to advanced palliative care in the early course of their hospitalization. Conclusions: Our experience of caring for these patients demonstrated a relatively lower mortality rate and higher survival rate in those with extracorporeal membrane oxygenation placement than previous reports from other countries and underscored the importance of proactive, advanced care planning in the early course of hospitalization.